Investigating water intrusions on cracked precast concrete wall panels through an experimental set-up and a computational fluid dynamics model under wind-driven rain conditions - Sadie, Homer T.; Diola, Nathaniel B. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Rainwater intrusions in building envelopes has been recognized as the primary source of materials deterioration inside the building and these occurrences are attributed to wind driven rain (WDR) and the inadequacies of general construction or design to ensure water tight building enclosures. The main objective of this study is to quantify the water ingress and its time to penetrate on through wall cracks as function of both the crack geometry (i.e. width and surface roughness) and the local WDR conditions. Computational fluid models, together with experimental set-ups about cracked concrete panel s of precast systems, derived from ASTM standards, provide some characterization quantities of water intrusions. Three areas of studies were integrated to come up with the computational fluid models using ANSYS FLUENT, which simulates WDR leakages on faulted through wall cracks. First, calculation of the localized wind driven rain test parameters was conducted. Second, cracked profiles from three-point bending test of concrete samples were studied calculating their roughness values from their digitized form. Thirdly, an experimental set up is facilitated, the result of which characterizes rain intrusion with input variables in the form of WDR loadings and crack displacements, it was also used validate the behavior of the computational model. Crack surface roughness in the form of fractal dimension is verified together with its impediment of flow through the cracks. C25 concrete samples registers the lowest fractal dimension of 1.354, having the highest leakage accumulated in comparison with both C30 with fractal dimension of 1.491 and C20 with fractal dimension of 1.480. Several characteristics of leakage behavior were observed: one, at 0.05 level of significance WDR loading is strongly correlated to accumulated volume of water leak; with the same level of significance, time for water ingress has an inverse association with WDR loading (Return Period). There is an indication that accumulated volume of leak is associated with crack displacement discounting the widest 2.0 mm crack displacement. Also, there is an indication of an inverse association of time for water ingress with crack displacement for a narrow range of crack displacemen
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Cracki